Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan pada PT. Indofood Sukses Makmur, Tbk - Asharun, Alfahira; Ramli, Anwar; Anwar; Idris, Abdi Akbar; Natsir, Uhud Darmawan (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2023)
This research purpose to determine the financial performance of PT Indofood Sukses Makmur, Tbk in 2018-2022 period using financial ratio analysis. The basis for assessing and achieving a company is through financial analysis so that the company can control its financial condition and create a company framework. In assessing the job prospects of a company in the past and future and assessing the achievements of a company, financial ratio analysis is used which includes liquidity ratios (current ratio), solvency ratios (debt to asset ratio), activity ratios (total asset turnover), profitability ratio (return on equity) and market ratio (earnings per share). This research is descriptive research which is studied quantitatively. The population of the research is all financial reports of PT. Indofood Sukses Makmur, Tbk is listed on the IDX in 2018-2022 period. The sample for this research is the financial position report and comprehensive income statement in 2018-2022 period. Data collection was carried out using documentation techniques. The results of this research found that the overall financial performance of PT. Indofood Sukses Makmur, Tbk in 2018-2022 period based on analysis of liquidity ratios and solvency ratios is in fairly good condition. Meanwhile, profitability ratios and market ratios are in good condition. However, regarding the activity ratio, the condition of PT. Indofood Sukses Makmur, Tbk is still not efficient so it can be said to be not good. This is due to an increase in sales and total assets during the 2018-2022 period. Based on the results of calculations and analysis of financial ratios, it can be concluded that the financial performance of PT. Indofood Sukses Makmur, Tbk in 2018-2022 period experiences growth in various aspects and profitability can increase, making the company profitable.